2022
DOI: 10.1146/annurev-marine-032221-090215
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Morphodynamics of Coastal Responses to Extreme Events: What Shape Are We In?

Abstract: This review focuses on recent advances in process-based numerical models of the impact of extreme storms on sandy coasts. Driven by larger-scale models of meteorology and hydrodynamics, these models simulate morphodynamics across the Sallenger storm-impact scale, including swash, collision, overwash, and inundation. Models are becoming both wider (as more processes are added) and deeper (as detailed physics replaces earlier parameterizations). Algorithms for wave-induced flows and sediment transport under shoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 263 publications
0
26
0
Order By: Relevance
“…Episodes of negative skewness drive offshore transport, which explains why the parameterized approach predicts a larger onshore wave-driven bedload than the direct method. While this work shows the efficacy of Ruessink's method in estimating asymmetric waveform characteristics, that approach relies on local measurements and does not account for shoaling history [29]. Other studies [59,60] have included non-local and offshore wave parameters to estimate wave asymmetry.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Episodes of negative skewness drive offshore transport, which explains why the parameterized approach predicts a larger onshore wave-driven bedload than the direct method. While this work shows the efficacy of Ruessink's method in estimating asymmetric waveform characteristics, that approach relies on local measurements and does not account for shoaling history [29]. Other studies [59,60] have included non-local and offshore wave parameters to estimate wave asymmetry.…”
Section: Discussionmentioning
confidence: 94%
“…In the presence of waves, morphodynamic models need to account for both suspended and bedload transport. Of the two modes of sediment transport, bedload transport is most affected by near-bottom wave orbital wave motions [29], thus necessitating the need to estimate asymmetric waveforms in modeling frameworks. Asymmetric waveforms can be computed by wave-resolving models [30,31], but these models are computationally expensive and impractical for regional-scale morphodynamic models.…”
Section: Introductionmentioning
confidence: 99%
“…Since it is widely observed that antecedent surf zone conditions are important in determining the magnitude of sub-aerial beach response during extreme events (e.g., a pronounced storm bar helps dissipate wave energy prior to eroding the sub-aerial beach; [28]), the lack of improved skill when using measured pre-storm data is likely due to inherent model structural errors in XBeach under the standard 1DH and surfbeat mode. While identifying the exact causes of these model structural errors is beyond the scope of this present work (refer [29] for further discussion), model behavior is explored by examining the adjustment in optimal model parameters obtained through the extensive GLUE calibration process. Figure 8 presents the optimal model parameters for each of the six bathymetries at Narrabeen and Duck, considering best performance across all three calibration storms at each site.…”
Section: Adjustment Of Optimal Model Parameters To Pre-storm Bathymetrymentioning
confidence: 99%
“…This is the opposite for the Upper bathymetry, where the GLUE calibration process is shown to favour model parameters that enhance sub-aerial beach erosion and compensate for the shallower surf zone (and, hence, less wave attack on the sub-aerial beach) artificially caused by this bathymetry. this present work (refer [29] for further discussion), model behavior is explored by examining the adjustment in optimal model parameters obtained through the extensive GLUE calibration process. Figure 8 presents the optimal model parameters for each of the six bathymetries at Narrabeen and Duck, considering best performance across all three calibration storms at each site.…”
Section: Adjustment Of Optimal Model Parameters To Pre-storm Bathymetrymentioning
confidence: 99%
“…Thus, linkage between the observed hydrodynamic conditions and the time series of morphological change remains difficult. Physics-based numerical modeling can effectively bridge this gap, and the state of morphodynamic modeling for these types of applications was recently reviewed in Sherwood et al (2021).…”
mentioning
confidence: 99%